2019
DOI: 10.1002/1873-3468.13470
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the lncRNA UCA1 and microRNAs in cancer

Abstract: Long non-coding RNAs (lncRNAs) are a major subset of highly conserved non-coding RNAs (ncRNAs) that consist of at least 200 nucleotides and have limited protein-coding potential. Cumulative data have shown that lncRNAs are deregulated in many types of cancer and may control pathophysiological processes of cancer at various levels, including transcription, post-transcription and translation. Recently, lncRNAs have been demonstrated to interact with microRNAs (miRNAs), another major subset of ncRNAs, which regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 141 publications
(210 reference statements)
1
21
0
Order By: Relevance
“…The Long non-coding RNA UCA1 was located in chromosome 9p13.12, and has been found to be overexpressed in tumor tissues, such as esophageal squamous cell carcinoma,colorectal cancer, ovarian cancer, bile duct carcinoma and melanoma etc. [16][17][18][19][20][21][22][23].UCA1 are participated in the tumorigenesis and progression, functioning as an oncogene [24][25][26][27][28][29][30]. However, the relation between UCA1 and renal cancer is still unknown and mysterious particularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Long non-coding RNA UCA1 was located in chromosome 9p13.12, and has been found to be overexpressed in tumor tissues, such as esophageal squamous cell carcinoma,colorectal cancer, ovarian cancer, bile duct carcinoma and melanoma etc. [16][17][18][19][20][21][22][23].UCA1 are participated in the tumorigenesis and progression, functioning as an oncogene [24][25][26][27][28][29][30]. However, the relation between UCA1 and renal cancer is still unknown and mysterious particularly.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences suggested that long non-coding RNAs (lncRNAs) perform important or vital functions in the malignant tumors [9][10][11][12][13][14][15]. LncRNA urothelial cancer associated 1 (UCA1) is abnormally expressed in esophageal squamous cell carcinoma, colorectal cancer, gastric cancer melanoma cells, pancreatic cancer, thyroid cancer, lung cancer and so on [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In vitro and in vivo assays were conducted to further explore its underlying roles in tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction is consistent with the associations of UCA1 with reductions in the 5-year disease-free survival in PC (n=130; HR, 2.88; 95% CI, 1.36-6.21; P= 0.007) (200) and in overall survival (n=40, P<0.001) (201). Additionally, the upregulation of UCA1 has also been shown to be a risk factor for the progression of ovarian cancer (202), gastric cancer (203), melanoma (204), pancreatic cancer (205), glioma (206) and others (207). Mechanistically, UCA1 facilitates PC at least in part through upregulations of ATF2 and CXCR4 by sponging miR-204 (208,209).…”
Section: Gene Expression-based Biomarkersmentioning
confidence: 99%
“…Mechanistically, UCA1 facilitates PC at least in part through upregulations of ATF2 and CXCR4 by sponging miR-204 (208,209). Intriguingly, UCA1 sequesters miR-204, leading to EMT in glioma, TGF-β signaling in oral cancer and Sox4 actions in esophageal cancer (207); UCA1 also sponges other miRNAs in promoting tumorigenesis in other cancer types (207). In this regard, the association of UCA1 with BCR could be strengthened by consideration of UCA1-regulated oncogenic factors.…”
Section: Gene Expression-based Biomarkersmentioning
confidence: 99%
“…11 Mechanistically, lncRNAs form regulatory networks with miRNAs and mRNAs or associate with RNA bind proteins to modulate their function. 12,13 Recent studies demonstrated that some lncRNAs participate in sorafenib resistance. For example, depletion of endogenous lncRNA TUC338 can target RASAL1 3ʹ-UTR and activate the RASAL1 pathway, which sensitizes HCC cells to the treatment of sorafenib.…”
Section: Introductionmentioning
confidence: 99%